Personhood as History: Māori Conversion in Light of the Polynesian Iconoclasm - Sissons, Jeffrey (Waka Kuaka, 2015)
In The Polynesian Iconoclasm: Religious Revolution and the Seasonality of Power (Berghann Books 2014) I described the desecration of god-images and temples during the period 1825-1828. I excluded Māori society from the analysis because there images were not as central to religious life and mass conversions to Christianity occurred in the 1840s. In this article I propose that the later mass conversion in event in New Zealand shared significant features with the Polynesian Iconoclasm. In both instances priests directed their ritual practice towards intense tapu centres, polluting chiefly bodies and triggering radical collective change.